CLINICAL EVALUATION OF SIDDHA VARMAM POINTS AND EXTERNAL MANIPULATIVE THERAPY FOR CHRONIC LOW BACK PAIN (THANDAGA VATHAM) - S. Sivakumar; Maheswari, D. Uma; Narayanan, Manimekalai (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Background: Thandaga Vatham, a clinical condition described in Siddha medicine, is characterized by lumbar pain radiating to the lower limbs and corresponds closely with lumbar spondylosis or mechanical low back pain in modern medicine. Middle-aged men engaged in occupations requiring prolonged standing or long-distance travel are particularly susceptible to this condition (Manchikanti et al., 2014; Brinjikji et al., 2015). Siddha Varmam therapy, which involves stimulation of vital energy points (Varmam pulligal), offers a unique therapeutic approach for musculoskeletal disorders (Elango, Arulmozhi, & Subramanian, 2018). Objective: This randomized controlled trial aimed to evaluate the efficacy of Siddha Varmam therapy combined with medicated oil massage in reducing pain, improving functional disability, and inducing radiological improvement in patients with Thandaga Vatham. Methods: Sixty male subjects aged 35 to 50 years with CT-confirmed Thandaga Vatham and chronic lumbar pain were randomized into two groups: Group A received Siddha Varmam therapy plus medicated oil massage, and Group B received standard lifestyle modification. Interventions were administered daily, five days a week, for 12 weeks. Primary outcome was functional disability assessed by the Quebec Back Pain Disability Scale (QBPDS). Secondary outcomes included pain intensity (Visual Analog Scale) and radiological changes via CT scan. Results: Repeated measures ANOVA revealed significant improvements in QBPDS scores in the experimental group compared to controls (F(2,116) = 23.67, p < .001). Pain intensity similarly decreased significantly (F(2,116) = 19.53, p < .001). Paired t-tests demonstrated significant radiological improvement in disc space height and facet joint degeneration in Group A (t(29) = 4.23, p < .001), with no significant changes in controls. These findings align with Siddha principles attributing therapeutic effects to Varmam point stimulation modulating neural and energy pathways (Subramanian, Arulmozhi, & Elango, 2016; Rajendran & Annamalai, 2019). Conclusion: Siddha Varmam therapy combined with medicated oil massage significantly reduces pain and disability and improves spinal structure in Thandaga Vatham patients. This integrative approach offers a promising complementary treatment for lumbar spondylosis, warranting further large-scale studies to confirm long-term benefits and underlying mechanisms.